THE VERIFICATION OF THE RSG-GAS REACTOR COOLING TOWER HEAT TRANSFER CAPACITY - Abdul Aziz Rohman Hakim (Jurnal Forum Nuklir, 2021)
The RSG-GAS reactor has been replaced and the technical specifications for the new cooling tower specify that the heat transfer capacity from the secondary cooling water to the environment is 5500 kW per module. Therefore, this study aims to verify the theoretical calculations of the heat transfer capacity using performance test data collected on the 30 MW power operation on December 20, 2018, such as the temperature of the primary and secondary coolant entering and exiting the cooling tower, wet bulb, and environmental dry bulb temperature, as well as the inlet and outlet air temperature. Furthermore, the data were used to calculate the heat transfer capacity from the secondary cooling water to the environment. The results showed that each cell of the RSG-GAS cooling tower reactor transfers the heat of approximately 5528.52 kW. This value is consistent with the technical specifications written in the revised RSG-GAS Safety Analysis Report 11.